"Smart Air purification: Enhancing Indoor Air quality using Arduino Uno and ThingSpeak Integration" - Sridhar, H S; Nuthana, V; Rakesh, K B (2024 International Conference on Smart Systems for applications in Electrical Sciences (ICSSES), 2024)
The Indoor air quality (IAQ) has become a growing concern due to the significant impact it has on human health and well-being. Traditional air purifiers offer solutions, but their efficiency and effectiveness often remain limited due to manual operation and lack of real-time monitoring capabilities. To address this issue, this paper proposes the development of Smart Air purifier system, integrating Arduino microcontroller technology with the ThingSpeak platform for enhanced IAQ monitoring and control. The proposed system employees Arduino as the central processing unit, with sensors for detecting various air pollutants and harmful gases such as CO, LPG etc., and temperature-humidity levels. These sensors continuously collect the data on IAQ parameters, which are then processed by the Arduino and transmitted to the ThingSpeak cloud platform using Wi-Fi connectivity.